Shema Israel Sebagai Identitas Iman: Kajian Teologis Ulangan 6:4 Pada Kehidupan Kristen Kontemporer - Mendrofa, Feri Aman; Zalukhu, Chung Washington Sukarno (JURNAL TABGHA, 2025)
Deuteronomy 6:4, widely known as the Shema Israel, is one of the most fundamental confessions of faith in the religious tradition of ancient Israel, affirming the exclusive oneness of YHWH. Although the text has been widely discussed in Indonesian theological scholarship, most existing studies approach it primarily from the standpoint of Christian religious education and family discipleship, while comprehensive treatment that integrates historical-critical inquiry, syntactic-lexical analysis, and contextual theological reflection remains limited. This article aims to fill that gap by analyzing the theological meaning of the Shema Israel in Deuteronomy 6:4 through a historical-critical approach and examining its relevance for Christians today. This study employs a qualitative method with a library-based biblical studies approach, integrating historical-contextual, grammatical-lexical, structural, and theological analysis of the Hebrew text. Data were drawn from primary sources (the Masoretic Hebrew text and its major translations) and secondary sources (lexicons, commentaries, and peer-reviewed theological journals), and were analyzed descriptively-interpretively. The findings show that the key terms shema and echad, together with the text’s tightly structured nominal syntax, express not merely a numerical claim about God’s singularity but an exclusive covenantal claim demanding total obedience. In the context of contemporary Christianity, this oneness of God carries renewed relevance amid secularism, moral relativism, and religious pluralism, which often manifest as subtler forms of idolatry. This study concludes that a proper understanding of the Shema Israel deepens Christian theological self-understanding and shapes an appropriately exclusive yet socially responsible faith commitment in the present context.